PENGARUH KESADARAN HALAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI (STUDI KASUS KFC KOTA SEMARANG) - Prasetyo, Puji Yuwanna (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2023)
Now a wide variety of food products are sold, making Muslim consumers have to be careful in choosing products, especially halal products. This study aims to examine and explain the effect of halal awareness on purchasing decisions with religiosity as a moderating variable. The existence of the religiosity variable is to find out whether it can moderate the level of consumer halal awareness. The higher the level of religiosity can affect the attitude of halal awareness of Muslim consumers in making product purchase decisions. The population in this study were Muslim consumers who had bought KFC products in the city of Semarang. The number of population is unknown and this study took a sample of 100 respondents with a purposive sampling approach. The type of data used is primary data with the method of collecting data through questionnaires. The analysis was carried out using Moderated Regression Analysis (MRA) using the SPSS 24 application. The results of this study indicate that respondents have a high level of awareness of halal, and that the effect of halal awareness on purchasing decisions is positive and significant. Finally, a high level of religiosity can strengthen the influence of awareness on purchasing decisions.